Covid 19 Pandemic: Assessment of Knowledge and Attitudes in Biomedical Waste Management among Health Care Professionals in Tamil Nadu - Ms Krithiga; Sudharsana V; Sribalaji R; Snega C (ACHSM, 2021)
Coronavirus, which was started provincially at Wuhan of China, has become a worldwide pandemic by affecting individuals of almost all the world. The developing pandemic of COVID-19 disease requires social distancing and individual cleanliness measures to secure general wellbeing. The aim of the present study is to evaluate the knowledge, attitude, practice and awareness of biomedical waste management in this pandemic situation among healthcare workers and medical students across Tamil Nadu. A cross sectional questionnaire survey was prepared to evaluate the knowledge regarding waste management and waste handling techniques. The survey found that most of the hospitals (50%) are using plastic containers for waste collection. Almost 79.7% of the respondents said they follow colour coding while disposing waste. When asked about exact category only few gave correct answers. Nearly 72.8% answered that they collect the Covid patient's wastes separately. As coronavirus is a contagious disease, each healthcare worker should be trained in safe handling of wastes. From this survey, it is clear that training about safe handling of waste is needed among workers. This survey will help government and healthcare providers to handle this Covid pandemic successfully and more effectively.